Understanding family communication across time zones - Cao, Xiang; Sellen, Abigail; Brush, A.J.; Kirk, Dave; Edge, Darren; Ding, Xianghua (Proceedings of CSCW 2010, 2010)
Nowadays it has become increasingly common for family members to be distributed in different time zones. These time differences pose specific challenges for communication within the family and result in different communication practices to cope with them. To gain an understanding of current challenges and practices, we interviewed people who regularly communicate with immediate family members living in other time zones. We report primary findings from the interviews, and identify design opportunities for improving the experience of cross time zone family communication.